2005
DOI: 10.1007/s00038-005-4097-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behaviours in smoking cessation among general practitioners in Finland 2001

Abstract: Minor differences in anti-smoking advice to patients between smoking and non-smoking general practitioners were found. The little involvement of GPs in health promotion activities regarding tobacco control is of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 18 publications
(18 reference statements)
2
32
0
6
Order By: Relevance
“…11,12,20 Generally, studies found that GPs who smoke report giving cessation advice less frequently than nonsmoking GPs, although not all studies supported this pattern. Studies in Austria, 21 Finland, 22 France, 23,24 and Greece 25 all found that non-smoking GPs were significantly more likely than smoking GPs to report that they raised the issue or advise quitting. However, a recent comparative study of 11 European Union (EU) countries concluded that while GPs who smoke tended to be less frequent in advising quitting, the difference was not significant.…”
Section: Gp Characteristicsmentioning
confidence: 99%
“…11,12,20 Generally, studies found that GPs who smoke report giving cessation advice less frequently than nonsmoking GPs, although not all studies supported this pattern. Studies in Austria, 21 Finland, 22 France, 23,24 and Greece 25 all found that non-smoking GPs were significantly more likely than smoking GPs to report that they raised the issue or advise quitting. However, a recent comparative study of 11 European Union (EU) countries concluded that while GPs who smoke tended to be less frequent in advising quitting, the difference was not significant.…”
Section: Gp Characteristicsmentioning
confidence: 99%
“…[1][2][3] Like their patients, however, some family doctors use tobacco, alcohol, and other addictive drugs. This could put themselves, their practices, and the health of the general population at risk; as such, private problems may become a wider social problem.…”
Section: Introductionmentioning
confidence: 99%
“…Physicians' role in health education is very important and is often expected to serve as role models for a healthy lifestyle (17,18). When Physicians have an unhealthy lifestyle, it might provide their patients with less effective advice on this topic than their more health-conscious colleagues (19,20).…”
Section: Introductionmentioning
confidence: 99%